ANALISIS SKENARIO KEMITRAAN KEHUTANAN ANTARA GAPOKTAN RIDING BERSATU DAN PT. BUMI MEKAR HIJAU (Suatu Kasus di Desa Riding Kecamatan Lampam Kabupaten Ogan Komiring Ilir, Provinsi Sumatera Selatan) - Purnawan, Handoyo Wahyu; Thayib, Hasroel; Abdini, Chairil (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2019)
Society and PT. BMH has an agreement on peat areas. Until now, forestry partnerships is not implemented. As lesson learning, scenario analysis analyzes driving factors, critical uncertainty driving factors, and composing a possible scenario in 2022. Critical uncertainty driving factor is the adaptive culture and policy alignment. Solution to solving environmental problems must position humans at the beginning,